Социетальная культура, ее основные формы и ценностная специфика: философский анализ - Сухина, Игорь; Suhina, Igor (Східноєвропейський національний університет імені Лесі Українки, 2013)
В статье представлен философский анализ феномена социетальной культуры как культуры интерсубъек-тивных человеческих отношений, ее культурогенной специфики, основных структурных форм и ценностного содержания. In article consideration and the philosophical analysis of a phenomenon of social culture as cultures of inter-subjective human relations, its cultural-creative specificity, the basic structural forms and the valuable maintenance is presented.
Societal Сulture, Іts Вasic Forms and Valuable Specificity: the Philosophical Analysis
Keywords: человек; man; сознание; consciousness; ценность; value; человеческие отношения; human relations; деятельность; human activity; культура; culture; социе-тальная культура; societal culture; общество; society